Technologies for developing a smart city in computational thinking. (2018) - Chen, Yinong; Luca, Gennaro De
Building a smart city involves almost all the aspects of social, economic, and technological issues. This paper gives a brief survey and overview of the latest technologies for building a smart city. It covers IoT, device as a service, service-oriented computing and cloud computing as the infrastructure, big data analysis and processing for data mining, and artificial intelligence. A visual programming language for IoT and robotics application development is also introduced, which offers a tool for architects and developers to define the applications using computational thinking and workflow of existing services and components.